Two New Triterpenoids from the Roots of Codonopsis pilosula - Zheng, Tao (Molecules, 2018)
Pseudolarolides U and V, two new triterpenoids, and four biogenetically related compounds, pseudolarolides E, F, K, and P were isolated from the roots of Codonopsis pilosula (Campanulaceae). Their structures were determined by spectroscopic data. The regulation of Sirtuin 1 (SIRT1) activity by all the isolated compounds was evaluated.